A Classroom Assignment for Sparking Discussion on the Role of Gender in Employee Compensation Decisions. (May 2022) - Waters, Gerald; Waymer, Damion
The following teaching brief outlines ways for advertising and public relations educators to discuss gender pay equity in the classroom. We know that educators are asked to teach about matters of diversity; yet many faculty members do not have adequate resources to do so. Faculty can rely on data and reports, but there are few hands-on activities that allow students to directly wrestle with gender pay disparity. The following activity centers on a hypothetical scenario in which we ask students to allocate pay bonuses to employees based on performance, time on the job, and other work-related factors. Over multiple semesters, we found that students consistently award smaller percentages of the bonus pool to employees with names commonly associated with females. Thus, this exercise provides a helpful way to enlighten students about implicit bias and gender pay equity in the professions of advertising and public relations.